MORPHO-SEMANTIC ANALYSIS IN NAMING OF ECOTOURISM IN BALI - Siti Setia Mintarsih (Fakultas Ilmu Budaya and LPPM Universitas Sebelas April, 2022)
This research presents the linguistics perspective on the naming of ecotourism in Bali. Bali is an island in Indonesia, located in South East Asia. Linguistics study employed to analyze the data are morphology and semantics. A research was conducted by identifying the names of ecotourism destinations in Bali, then they were analyzed based on the word formation studies. The meanings or messages of the destinations’ names are discussed with the semantics study with metaphors. This research is using word formation theory by Yule and meaning with metaphors by Newmark. This research using qualitative descriptive method by using triangulation theory, those are interview and library research. This research aims to describe the types of word formation process and to explain the meaning of ecotourism names in Bali. The results of this research show there are 5 morphological process in naming of ecotourism in Bali, such as borrowing, blending, compounding, acronym, and conversion. In addition, from 5 morphological process, borrowing is used dominantly. In the semantics study, the names of ecotourism in Bali mean the physical characteristics of the nature, tourism destination, location of the destination, and activity in the destination.